Higienização em prótese sobre implante - Bannwart, Lisiane Cristina [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Pereira, Leonardo Viana [UNESP]; Pellizzer, Eduardo Pizza [UNESP] (My University, 2012)
With the advances of osseointegration principles, the use of implant-supported prosthesis has become a routine treatment option. The success of an implant is initially associated to the surgical technique, primary stability and absence of bacterial contamination on the implant site. Subsequently, the absence of mechanical trauma (overload) and peri-implantitis are sine qua non conditions to the longitudinal success of implant treatment. Therefore, the strict maintenance of oral hygiene is highly important to avoid biofilm accumulation around the implant and consequently to provide last-long implant-supported dentures. The clinician has the responsibility to supply a favorable prognosis to the patient so that the rehabilitation succeed. For this reason, during prosthesis fabrication the clinician should observe the design and emergency profile of the prosthesis, the peri-implant sulcus depth as well as the presence of motor or psychological impairment by the patient. Subjects with missing teeth and that will be submitted to the implant treatment should be motivated and adequate instructed regarding oral hygiene and its importance since the best option to obtain treatment longevity and consequently patient’s satisfaction is the prevention. Therefore, this study aimed to perform a literature review about the hygiene of implant-supported prosthesis.

Com a evolução dos princípios da osseointegração as próteses implantossuportadas estão se transformando em uma opção rotineira de tratamento. O sucesso de um implante está associado inicialmente à técnica cirúrgica, a estabilidade primária e a ausência de contaminação bacteriana do implante. Posteriormente, a ausência de trauma mecânico ou sobrecarga e periimplantite são fundamentais para esse sucesso. Portanto, para que a reabilitação com próteses implantossuportadas seja adequada, a manutenção rigorosa de higiene oral é necessária para evitar o acumulo de placa bacteriana ao redor do implante. A principal responsabilidade do cirurgião em relação aos pacientes que serão reabilitados é fornecer um prognóstico favorável a longo prazo. Para isso, durante a confecção da prótese o protesista deve observar o design e o perfil de emergência da prótese, a profundidade do sulco periimplantar e também ocorrência de distúrbio motor ou psicológico por parte do paciente. Os indivíduos que perderam dentes e serão submetidos à esse tipo de reabilitação necessitam de motivação e instrução adequada em relação à higienização e sua importância, pois a melhor maneira de se obter longevidade da prótese e conseqüentemente a satisfação do paciente em relação ao tratamento é a prevenção. Diante do exposto, o objetivo do presente trabalho foi realizar uma revisão de literatura sobre higienização em prótese sobre implante.
Hygiene in implant denture
Keywords: Dental implantation; Oral hygiene; Dental prosthesis; Implante dentário; Higiene bucal; Prótese dentária